Size variation in Tachyoryctes splendens (East African mole-rat) and its implications for late Quaternary temperature change in equatorial East Africa. (15th May 2016) - Faith, J. Tyler; Patterson, David B.; Blegen, Nick; O'Neill, Chris J.; Marean, Curtis W.; Peppe, Daniel J.; Tryon, Christian A.
Abstract: This study develops a new proxy for Quaternary temperature change in tropical Africa through analysis of size variation in East African mole-rat ( Tachyoryctes splendens ). In modern mole-rats, mandibular alveolar length is unrelated to annual precipitation, precipitation seasonality, temperature seasonality, or primary productivity. However, it is inversely correlated with mean annual temperature, in agreement with Bergmann's rule. This relationship is observed at temperatures below ∼17.3 °C, but not at higher temperatures. We apply these observations to late Quaternary mole-rats from Wakondo (∼100 ka) and Kisaaka (∼50 ka) in the Lake Victoria region and Enkapune ya Muto (EYM; ∼7.2–3.2 ka) in Kenya's central rift. The Lake Victoria mole-rats are larger than expected for populations from warm climates typical of the area today, implying cooler temperatures in the past. The magnitude of temperature decline needed to drive the size shift is substantial (∼4–6 °C), similar in magnitude to the degree of change between the Last Glacial Maximum and Holocene, but is consistent with regional temperature records and with scenarios linking equatorial African temperature to northern hemisphere summer insolation. Size changes through time at EYM indicate that rising temperatures during the middle Holocene accompanied and potentially contributed to a decline in Lake Naivasha and expansion of grassland vegetation. Highlights: Body size of modern T achyoryctes splendens tracks mean annual temperature. Body size of fossil mole-rats can be used to track past temperature changes. Mole-rats from near Lake Victoria indicate cooler temperatures at ∼50 ka and ∼100 ka. Mole-rats from near Lake Naivasha indicate mid-Holocene warming.